Safeguarding Public Values by Design: A Socio-Technical Approach to Digital Twins in Regional Spatial Planning Under the Environmental Planning Act - van Meerten, John (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
In the context of climate change and housing challenges, Digital Twins (DTs) are a promising technology. However, there is little experience regarding good use of this technology. This research proposal explores how DTs can safeguard public values in spatial planning under the Environmental Planning Act (Omgevingswet). Combining a socio-technical perspective with Value-Sensitive Design (VSD), the study focuses on integrating values into DT technology. Expected studies include identifying key values, designing a normative framework, and measuring its impact. This contributes to improved decision-making and spatial planning by regional governments.